A Comparative Study of Seismic Behavior of High Rise Building with Diagrid Structure and Conventional RCC Framed Structure - Behera, Ajaya Kumar; Parhi, P. K. (AMC Indian Journal of Civil Engineering, 2023)
Construction of tall buildings with various structural systems is on the rise these days. Due to its adaptability and attractive look, the Diagrid system is a prominent technology in high-rise buildings. In this study, a structural model of 32 storey buildings is analyzed using the ETAB software, and various metrics, such as storey stiffness, storey displacement, storey shear, and storey drift in different seismic zones are derived. Comparison is done among these parameters for 36 different cases and the best of the configuration is found out. Study of the these parameters is done by adopting Response Spectrum Method for Zone II and Zone V. This study concludes that the square shaped building with 2-storey module diagrid column shows less displacement, less storey drift and higher stiffness among all the considered cases.